IMPLEMENTASI SEKOLAH RAMAH ANAK KOMPONEN SARANA PRASARANA DALAM MENUNJANG PEMBELAJARAN DI SEKOLAH DASAR - Zie Zie, Yildiz; Suharjuddin (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
This study aims to analyze the implementation of facilities and infrastructure in child-friendly schools at SDN Bekasi Jaya I Bekasi City and to find out the supporting and inhibiting factors from the fulfillment and utilization of facilities and infrastructure in the implementation of facilities and infrastructure in child-friendly schools at SDN Bekasi Jaya I Bekasi City. This research uses a type of qualitative research with a case study approach, this data collection technique uses interviews, observation and documentation, data sources in the study are obtained from primary and secondary data. The results of this study are (1) Utilization of child-friendly school infrastructure in supporting learning at SDN Bekasi Jaya I, namely by utilizing the classroom by arranging it as well as possible so that learning becomes fun, (2) utilization of the library space as a learning resource is also utilized by lending books to students according to their needs and then recorded and returned with a certain time limit. (3) the utilization of the uks room as a place of first aid for students is to take them to the uks room and then given medicine. While the supporting factors for facilities and infrastructure are cooperation with other parties, both internal and external parties, while the inhibiting factors for the fulfillment and utilization of infrastructure facilities are the lack of support by parents of students and limited human resources.